Automatic segmentation for right ventricular (RV) based on endocardial contour extraction in echocardiography image sequences - O. K. Rahmat, Rahmita Wirza; Abed Ali Dawood, Faten; Dimon, Mohd Zamrin; Kadiman, Suhaini; Abdullah, Lili Nurliyana (2012)
The present invention relates to a method of processing a three-dimensional (3D) echocardiography video with a complete cardiac cycle encompassing a ventricular. The method comprises step of obtaining a set of voxels representing a total scanned volume from the three-dimensional (3D) echocardiography video and performing segmentation on the set of voxels representing the total scanned volume.